MODEL INOVATIF PEMBINAAN KARAKTER ISLAMI UNTUK ANAK BERKEBUTUHAN KHUSUS DI MI MUHAMMADIYAH 2 PONOROGO - Fachma Nur Ahsani; Oktaviadina Astiari; Nurul Iman; Katni (LPPM IAD Probolinggo, 2025)
This research explores an innovative model of Islamic character building for children with special needs at MI Muhammadiyah 2 Ponorogo, particularly those diagnosed with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). The study is motivated by the urgent need to develop inclusive Islamic education that not only provides access but also ensures meaningful participation and spiritual growth for neurodiverse learners. Using a qualitative case study approach, the data were obtained through in-depth interviews with teachers, school leaders, and parents, participant and non-participant observations of daily religious activities, as well as documentation of school programs. Data analysis was conducted through the Miles and Huberman model involving data reduction, data display, verification, and triangulation to ensure validity and credibility. The findings indicate that Islamic character formation is effectively carried out through consistent religious habituation, including congregational prayers, Qur’an recitation, memorization of short surahs, and daily prayer practices. These activities are strengthened by differentiated teaching strategies that adapt to the cognitive and behavioral characteristics of students with ASD and ADHD. The research highlights the central role of teachers as role models, the influence of a supportive school culture, and the involvement of families as critical supporting factors. Nevertheless, the study also identifies several challenges, such as limited teacher competence in inclusive religious pedagogy and difficulties in managing diverse behavioral responses of students.This study contributes both theoretically and practically to the discourse of inclusive Islamic education by presenting a holistic and humanistic model that integrates spiritual values, moral exemplification, and adaptive pedagogical practices. The model not only emphasizes religious habituation but also encourages empathy, patience, and collaboration among educators, parents, and peers. Therefore, the findings provide valuable insights for policymakers, Islamic educators, and inclusive schools in designing and implementing religious character education that is equitable, contextual, and transformative. Keywords: Religious character, ADHD, ASD, inclusive education, Islamic education